Low-expansion porous silicon carbon material and preparation method thereof

By using a low-expanded porous silicon carbon material preparation method in lithium-ion batteries, and using high crosslinking polyvinyl carbonate for carbonization coating, the carbon layer of silicon carbon anode material is easily cracked during charging and discharging. Problem, improving the cycling performance and mechanical strength of the battery.

CN119324208APending Publication Date: 2025-01-17XIANTAO HAIRONG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410757925.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Due to the low crosslinking degree and poor flexibility and mechanical properties of the carbon layer of silicon carbon anode material in existing lithium-ion batteries, the carbon layer of the silicon carbon anode material is prone to cracking and pulverization of the electrode during the charging and discharging process, affecting the circulation. performance.

Method used

Using low-expanded porous silicon carbon material and its preparation method, SiH4 is deposited in a rotary kiln by porous carbon particles, and then water bath heated with FEC and alkyl lithium oxide to form vinylene carbonate, and polymerized under the initiator to form crosslinking degree The high polyvinyl carbonate is subjected to carbonization coating to form a strong toughness coating.

Benefits of technology

It improves the circulation performance of silicon carbon negative electrode, alleviates the carbon layer rupture and pole sheet powdering caused by silicon expansion, enhances mechanical strength, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324208A_ABST
    Figure CN119324208A_ABST
Patent Text Reader

Abstract

The invention discloses a low-expansion porous silicon carbon material and a preparation method thereof, and relates to the technical field of lithium ion batteries. According to the low-expansion porous silicon carbon material and the preparation method thereof, S1, porous carbon is selected, the specific surface area is 1500-2500m < 2 > / g, the particle size is 2-10mu m, and the aperture is 1-5nm; s2, feeding the porous carbon particles into a rotary kiln bed, vacuumizing a deposition area of a rotary kiln under protective gas, and introducing SiH4 for deposition to obtain a porous silicon carbon precursor; s3, FEC is selected as a coating precursor, the FEC and alkyl lithium oxide are subjected to water bath heating, the temperature is 45-80 DEG C, and the time is 2-4 h; s4, heating the purified vinylene carbonate to a melting state of 30 DEG C, adding an AIBN initiator, and heating to 50-80 DEG C for 5-10 hours to obtain poly (vinylene carbonate); and S5, uniformly mixing the obtained vinylene carbonate and the silicon carbon precursor, raising the temperature to the highest temperature, and keeping the temperature for 15-24 hours to obtain the porous silicon carbon coated with the vinylene carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a low-expansion porous silicon-carbon material and a preparation method thereof. Background Art

[0002] With the development of new energy technologies, the energy density requirements for lithium-ion batteries will become higher and higher in the future. The theoretical capacity of graphite negative electrode is only 372mAh / g, which has basically reached its limit and it is difficult to make further breakthroughs. To further improve the energy density of the battery, it is necessary to redesign it from the perspective of materials. The capacity of silicon-based negative electrode is relatively high, and its theoretical capacity can reach 4200mAh / g (Li4.4 Si). However, due to its volume expansion and easy pulverization during the cycle, the cycle performance decreases during the battery charging and discharging process, thus affecting the commercial value of silicon-based negative electrode. The commonly used solution in the market is CVD gas phase coating. Through the carbonization of the gas phase carbon layer, a dense carbon layer is formed on the surface of silicon carbon, thereby restraining the volume expansion of silicon. However, the carbon layer formed by this method has a low degree of cross-linking, poor flexibility and mechanical properties. With the repeated charge and discharge expansion of silicon carbon, the coated carbon layer is prone to cracking and the pole piece is pulverized, thereby affecting the cycle performance. Summary of the invention

[0003] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a low-expansion porous silicon-carbon material and a preparation method thereof, which can solve the problem that the carbon layer has a low degree of cross-linking, poor flexibility and mechanical properties, and as the silicon-carbon expands during repeated charge and discharge, the coated carbon layer is prone to cracking and the pole piece is powdered, thereby affecting the cycle performance.

[0004] To achieve the above object, the present invention provides the following technical solutions: a low expansion porous silicon carbon material and a preparation method thereof, comprising the following steps: S1: selecting a porous carbon with a specific surface area of ​​1500-2500m2 / g, a particle size of 2-10um, and a pore size of 1-5nm;

[0005] S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor;

[0006] S3 selects FEC as a coating precursor, heats it with alkyl lithium oxide in a water bath at a temperature of 45-80°C for 2-4 hours, and then obtains vinylene carbonate by distillation-crystallization;

[0007] S4: heating the purified vinylene carbonate to a melting state at 30°C, adding an AIBN initiator, and heating to 50-80°C for 5-10 hours to obtain polyvinylene carbonate;

[0008] S5: uniformly mixing the obtained polyvinylene carbonate and silicon carbon precursor, heating to 600-900° C. for carbonization coating treatment, with a heating rate of 5-10° C., heating to the highest temperature and then keeping the temperature for 15-24 hours to obtain porous silicon carbon coated with polyvinylene carbonate;

[0009] S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, which is charged and discharged at a rate of 0.5C / 0.5C.

[0010] Preferably, the gas flow rate of the S2 silicon source is 50-100 mL / min, the heating rate is 1-5°C / min, the maximum temperature is raised to 800-950°C, and after keeping the temperature for 3-6 hours, it is quickly cooled to room temperature.

[0011] Preferably, if the temperature of S3 is too low, less vinylene carbonate will be generated; if the temperature is too high, the energy consumption will be high; if the time is too short, less vinylene carbonate will be generated; if the time is too long, the energy consumption will be high.

[0012] Preferably, if the temperature of S4 is too low, the cross-linking degree of the generated polyvinylene carbonate is low; if the temperature is too high, the energy consumption is high; if the time is too short, the cross-linking degree of the generated polyvinylene carbonate is low; if the time is too long, the energy consumption is high.

[0013] Preferably, S6 records the expansion rate of cycles at different stages and the capacity retention rate of cycles at different numbers.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] (1) The low expansion porous silicon-carbon material and its preparation method. The coating agent used in this method is different from the conventional CVD gas phase coating. The polymer has a high degree of cross-linking, strong toughness, and high mechanical strength. It can be used as a coating raw material for silicon-carbon materials, and can effectively alleviate the carbon layer rupture and pole piece pulverization caused by silicon expansion, thereby improving the cycle performance of the silicon-carbon negative electrode.

[0016] (2) The low expansion porous silicon-carbon material and its preparation method adopt a fluoroethylene carbonate type fluorocyclic ester compound to react with an alkoxy compound to generate a cyclic unsaturated ester compound, and then polymerize it under an initiator to generate a polycarbonate polymer. This polymer has a high degree of cross-linking, strong toughness, and high mechanical strength. It can be used as a coating raw material for silicon-carbon materials, can effectively alleviate the carbon layer rupture and pole piece pulverization caused by silicon expansion, and improve the cycle performance of the silicon-carbon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention is further described below in conjunction with the accompanying drawings and embodiments:

[0018] Figure 1 is a reaction equation for preparing a low expansion porous silicon-carbon material coating agent of the present invention;

[0019] Figure 2 This is a cycle comparison diagram of an embodiment and a comparative example of a low expansion porous silicon-carbon material of the present invention. DETAILED DESCRIPTION

[0020] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.

[0021] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0022] In the description of the present invention, "greater than", "less than", "exceed" etc. are understood as not including the number itself, and "above", "below", "within" etc. are understood as including the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0023] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.

[0024] See also Figure 1-2 , the present invention provides a technical solution: a low expansion porous silicon carbon material and a preparation method thereof, comprising the following steps, S1 selects a porous carbon with a specific surface area of ​​1500-2500m2 / g, a particle size of 2-10um, and a pore size of 1-5nm;

[0025] S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor;

[0026] The gas flow rate of the silicon source is 50-100 mL / min, the heating rate is 1-5°C / min, the maximum temperature is raised to 800-950°C, and after keeping the temperature for 3-6 hours, it is quickly cooled to room temperature.

[0027] S3 selects FEC as the coating precursor and heats it with alkyl lithium oxide in a water bath at a temperature of 45-80°C for 2-4 hours. If the temperature is too low, less vinylene carbonate will be generated; if the temperature is too high, the energy consumption will be high. If the time is too short, less vinylene carbonate will be generated; if the time is too long, the energy consumption will be high. Then, vinylene carbonate is obtained by distillation-crystallization.

[0028] Methods S1, S2 and S3 include but are not limited to the synthesis of other cyclic unsaturated ester compounds, such as propylene carbonate, butylene carbonate, etc., or a mixture of two or more thereof; the coating precursor includes but is not limited to other fluorinated cyclic ester compounds, such as fluorinated propylene carbonate, fluorinated butylene carbonate, etc., or a mixture of two or more thereof, and the reaction equation is as follows: Figure 1 As shown;

[0029] S4: heating the purified vinylene carbonate to a melting state at 30°C, adding an AIBN initiator, and heating to 50-80°C for 5-10 hours to obtain polyvinylene carbonate;

[0030] If the temperature is too low, the cross-linking degree of the generated polyvinylene carbonate is low; if the temperature is too high, the energy consumption is high. If the time is too short, the cross-linking degree of the generated polyvinylene carbonate is low; if the time is too long, the energy consumption is high.

[0031] The above method includes but is not limited to other polycyclic olefin carbonate compounds, such as polypropylene carbonate, polybutylene carbonate, etc., one or a mixture of two or more thereof, and the polymerization reaction equation is as follows: Figure 1 shown.

[0032] S5: uniformly mix the obtained polyvinyl carbonate and silicon carbon precursor, heat to 600-900°C for carbonization coating treatment, with a heating rate of 5-10°C, and keep the temperature for 15-24h after heating to the highest temperature to obtain porous silicon carbon coated with polyvinyl carbonate.

[0033] The above-mentioned method includes but is not limited to porous silicon carbon coated with other polycyclic olefin carbonate compounds.

[0034] S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, and the battery is charged and discharged at 0.5C / 0.5C, and the expansion rate at different stages of the cycle and the capacity retention rate at different cycle numbers are recorded.

[0035] Embodiment 1

[0036] S1 uses a porous carbon with a specific surface area of ​​1800m2 / g, a particle size of 5um, and a pore size of 3nm;

[0037] S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor;

[0038] The gas flow rate of the silicon source was 70 mL / min, the heating rate was 3° C. / min, the maximum temperature was raised to 850° C., and after being kept for 4 hours, it was rapidly cooled to room temperature.

[0039] S3 selects FEC as the coating precursor and heats it with alkyl lithium oxide in a water bath at 60°C for 3 hours. If the temperature is too low, less vinylene carbonate will be generated; if the temperature is too high, the energy consumption will be high. If the time is too short, less vinylene carbonate will be generated; if the time is too long, the energy consumption will be high. Then vinylene carbonate is obtained by distillation-crystallization;

[0040] Methods S1, S2 and S3 include but are not limited to the synthesis of other cyclic unsaturated ester compounds, such as propylene carbonate, butylene carbonate, etc., or a mixture of two or more thereof; the coating precursor includes but is not limited to other fluorinated cyclic ester compounds, such as fluorinated propylene carbonate, fluorinated butylene carbonate, etc., or a mixture of two or more thereof, and the reaction equation is as follows: Figure 1 As shown;

[0041] S4: heating the purified vinylene carbonate to a melting state at 30°C, adding an AIBN initiator, and heating to 65°C for 7 hours to obtain polyvinylene carbonate;

[0042] If the temperature is too low, the cross-linking degree of the generated polyvinylene carbonate is low; if the temperature is too high, the energy consumption is high. If the time is too short, the cross-linking degree of the generated polyvinylene carbonate is low; if the time is too long, the energy consumption is high.

[0043] The above method includes but is not limited to other polycyclic olefin carbonate compounds, such as polypropylene carbonate, polybutylene carbonate, etc., one or a mixture of two or more thereof, and the polymerization reaction equation is as follows: Figure 1 shown.

[0044] S5: Evenly mix the obtained polyvinyl carbonate and silicon carbon precursor, heat to 750°C for carbonization coating treatment, with a heating rate of 7°C. After heating to the highest temperature, keep the temperature for 20 hours to obtain porous silicon carbon coated with polyvinyl carbonate.

[0045] The above-mentioned method includes but is not limited to porous silicon carbon coated with other polycyclic olefin carbonate compounds.

[0046] S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, and the battery is charged and discharged at 0.5C / 0.5C, and the expansion rate at different stages of the cycle and the capacity retention rate at different cycle numbers are recorded.

[0047] Embodiment 2:

[0048] S1 uses a porous carbon with a specific surface area of ​​1500m2 / g, a particle size of 2um, and a pore size of 1nm;

[0049] S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor;

[0050] The gas flow rate of the silicon source was 50 mL / min, the heating rate was 1° C. / min, the maximum temperature was raised to 800° C., and after being kept for 3 hours, it was rapidly cooled to room temperature.

[0051] S3 selects FEC as the coating precursor and heats it with alkyl lithium oxide in a water bath at 45°C for 2 hours. If the temperature is too low, less vinylene carbonate will be generated; if the temperature is too high, the energy consumption will be high. If the time is too short, less vinylene carbonate will be generated; if the time is too long, the energy consumption will be high. Then vinylene carbonate is obtained by distillation-crystallization;

[0052] Methods S1, S2 and S3 include but are not limited to the synthesis of other cyclic unsaturated ester compounds, such as propylene carbonate, butylene carbonate, etc., or a mixture of two or more thereof; the coating precursor includes but is not limited to other fluorinated cyclic ester compounds, such as fluorinated propylene carbonate, fluorinated butylene carbonate, etc., or a mixture of two or more thereof, and the reaction equation is as follows: Figure 1 As shown;

[0053] S4: heating the purified vinylene carbonate to a melting state at 30°C, adding an AIBN initiator, and heating to 50°C for 5 hours to obtain polyvinylene carbonate;

[0054] If the temperature is too low, the cross-linking degree of the generated polyvinylene carbonate is low; if the temperature is too high, the energy consumption is high. If the time is too short, the cross-linking degree of the generated polyvinylene carbonate is low; if the time is too long, the energy consumption is high.

[0055] The above method includes but is not limited to other polycyclic olefin carbonate compounds, such as polypropylene carbonate, polybutylene carbonate, etc., one or a mixture of two or more thereof, and the polymerization reaction equation is as follows: Figure 1 shown.

[0056] S5: The obtained polyvinyl carbonate and silicon carbon precursor are mixed evenly, and heated to 600°C for carbonization coating treatment, with a heating rate of 5°C. After heating to the highest temperature, the temperature is kept for 15 hours to obtain porous silicon carbon coated with polyvinyl carbonate.

[0057] The above-mentioned method includes but is not limited to porous silicon carbon coated with other polycyclic olefin carbonate compounds.

[0058] S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, and the battery is charged and discharged at 0.5C / 0.5C, and the expansion rate at different stages of the cycle and the capacity retention rate at different cycle numbers are recorded.

[0059] Embodiment three:

[0060] S1 uses a porous carbon with a specific surface area of ​​2500m2 / g, a particle size of 10um, and a pore size of 5nm;

[0061] S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor;

[0062] The gas flow rate of the silicon source was 100 mL / min, the heating rate was 5°C / min, the maximum temperature was raised to 950°C, and after keeping the temperature for 6 hours, it was quickly cooled to room temperature.

[0063] S3 selects FEC as the coating precursor and heats it with alkyl lithium oxide in a water bath at 80°C for 4 hours. If the temperature is too low, less vinylene carbonate will be generated; if the temperature is too high, the energy consumption will be high. If the time is too short, less vinylene carbonate will be generated; if the time is too long, the energy consumption will be high. Then vinylene carbonate is obtained by distillation-crystallization;

[0064] Methods S1, S2 and S3 include but are not limited to the synthesis of other cyclic unsaturated ester compounds, such as propylene carbonate, butylene carbonate, etc., or a mixture of two or more thereof; the coating precursor includes but is not limited to other fluorinated cyclic ester compounds, such as fluorinated propylene carbonate, fluorinated butylene carbonate, etc., or a mixture of two or more thereof, and the reaction equation is as follows: Figure 1 As shown;

[0065] S4: heating the purified vinylene carbonate to a melting state at 30°C, adding an AIBN initiator, and heating to 80°C for 10 hours to obtain polyvinylene carbonate;

[0066] If the temperature is too low, the cross-linking degree of the generated polyvinylene carbonate is low; if the temperature is too high, the energy consumption is high. If the time is too short, the cross-linking degree of the generated polyvinylene carbonate is low; if the time is too long, the energy consumption is high.

[0067] The above method includes but is not limited to other polycyclic olefin carbonate compounds, such as polypropylene carbonate, polybutylene carbonate, etc., one or a mixture of two or more thereof, and the polymerization reaction equation is as follows: Figure 1 shown.

[0068] S5: Evenly mix the obtained polyvinyl carbonate and silicon carbon precursor, heat to 900°C for carbonization coating treatment, with a heating rate of 10°C. After heating to the highest temperature, keep the temperature for 24 hours to obtain porous silicon carbon coated with polyvinyl carbonate.

[0069] The above-mentioned method includes but is not limited to porous silicon carbon coated with other polycyclic olefin carbonate compounds.

[0070] S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, and the battery is charged and discharged at 0.5C / 0.5C, and the expansion rate at different stages of the cycle and the capacity retention rate at different cycle numbers are recorded.

[0071] Furthermore, the coating agent used in this method is different from conventional CVD gas phase coating. This polymer has a high degree of cross-linking, strong toughness, and high mechanical strength. It can be used as a coating raw material for silicon-carbon materials, and can effectively alleviate the carbon layer rupture and pole piece pulverization caused by silicon expansion, thereby improving the cycle performance of the silicon-carbon negative electrode.

[0072] Comparative Example 1:

[0073] S1 uses a porous carbon with a specific surface area of ​​1800m2 / g, a particle size of 5um, and a pore size of 3nm;

[0074] S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor;

[0075] The gas flow rate of the silicon source was 70 mL / min, the heating rate was 3° C. / min, the maximum temperature was raised to 850° C., and after being kept for 4 hours, it was rapidly cooled to room temperature.

[0076] S3 selected C2H2 as the coating gas source, heated to 750℃ for carbonization coating treatment, with a heating rate of 7℃. After heating to the highest temperature, it was kept warm for 20h to obtain gas-phase coated porous silicon carbon.

[0077] S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, and the battery is charged and discharged at 0.5C / 0.5C, and the expansion rate at different stages of the cycle and the capacity retention rate at different cycle numbers are recorded.

[0078] The embodiments of the present invention are described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the technical field without departing from the purpose of the present invention.

Claims

1. A low expansion porous silicon carbon material and a preparation method thereof, characterized in that: The following steps are included: S1 uses a porous carbon with a specific surface area of ​​1500-2500m2 / g, a particle size of 2-10um, and a pore size of 1-5nm; S2: delivering the porous carbon particles to a rotary kiln bed, and under protective gas, evacuating the rotary kiln deposition area and introducing SiH4 for deposition to obtain a porous silicon-carbon precursor; S3 selects FEC as a coating precursor, heats it with alkyl lithium oxide in a water bath at a temperature of 45-80°C for 2-4 hours, and then obtains vinylene carbonate by distillation-crystallization; S4: heating the purified vinylene carbonate to a melting state at 30°C, adding an AIBN initiator, and heating to 50-80°C for 5-10 hours to obtain polyvinylene carbonate; S5: uniformly mixing the obtained polyvinylene carbonate and silicon carbon precursor, heating to 600-900° C. for carbonization coating treatment, with a heating rate of 5-10° C., heating to the highest temperature and then keeping the temperature for 15-24 hours to obtain porous silicon carbon coated with polyvinylene carbonate; S6 uses the negative electrode material and graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet for testing capacity. At the same time, it is matched with the NCM positive electrode to make a battery, which is charged and discharged at a rate of 0.5C / 0.5C.

2. A low expansion porous silicon carbon material and a preparation method thereof according to claim 1, characterized in that: The gas flow rate of the S2 silicon source is 50-100 mL / min, the heating rate is 1-5°C / min, the maximum temperature is raised to 800-950°C, and after keeping the temperature for 3-6 hours, it is quickly cooled to room temperature.

3. The low expansion porous silicon-carbon material and the preparation method thereof according to claim 1, characterized in that: If the temperature of S3 is too low, less vinylene carbonate will be generated; if the temperature is too high, the energy consumption will be high. If the time is too short, less vinylene carbonate will be generated; if the time is too long, the energy consumption will be high.

4. The low expansion porous silicon-carbon material and the preparation method thereof according to claim 1, characterized in that: If the temperature of S4 is too low, the cross-linking degree of the generated polyvinylene carbonate is low; if the temperature is too high, the energy consumption is high. If the time is too short, the cross-linking degree of the generated polyvinylene carbonate is low; if the time is too long, the energy consumption is high.

5. The low expansion porous silicon-carbon material and the preparation method thereof according to claim 1, characterized in that: The S6 records the expansion rate of the cycles at different stages and the capacity retention rate of the cycles at different numbers.